Implementation of Tasawwuf Values ​​in the Book of Durratun Nashihin to Improve the Spirituality of Students at the Lubabul Fattah Islamic Boarding School Tulungagung - Syaiful Rijal; Nabila Rahma Al Aghna; Ahmad Saddad (JIA (Jurnal Ilmu Agama), 2024)
Efforts to increase the spirituality of students at the Lubabul Fattah Islamic Boarding School are actualized through daily activities based on the values ​​of Sufism in the book Durratun Nashihin. This implementation effort was carried out with the hope that there would be an improvement in the students' morals, self-awareness and empathy. This research uses descriptive qualitative methods. Thus, this research produces a conclusion that the Sufism values ​​contained in the book Durratun Nashihin which have been practiced by the students of the Lubabul Fattah Islamic Boarding School have had a positive impact in increasing spirituality, especially in terms of morals, morals, empathy and tolerant attitudes. These values ​​include patience, tawadhu', sadaqah fi sabilillah, congregational prayer, reading the Qur’an and dhikr. In the implementation process, the Lubabul Fattah Islamic Boarding School has done this through an educational curriculum, so that the students' understanding of Sufism is not only through spiritual practice, but also through educational pathways which have their own implications for the soul/spirituality of a student as evidenced by attitudes and behavior that show calm.